2000
DOI: 10.3354/meps202163
|View full text |Cite
|
Sign up to set email alerts
|

Development of swimming abilities in reef fish larvae

Abstract: Recent studies have revealed that reef fish larvae have excellent sustained swimming capabilities and considerable potential for modifying their dispersal patterns by active swimming. However, these studies concentrate solely on the late pelagic phase. We examined the development of swimming abilities from hatching through to settlement in 3 reef fish species (Pomacentrus amboinensis, Sphaeramia nematoptera, Amphiprion melanopus). Larval rearing provided larvae at all stages of development. Experiments were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
199
6
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(219 citation statements)
references
References 32 publications
13
199
6
1
Order By: Relevance
“…Ohlberger et al (2006) verified that Mugil cephalus Linnaeus, 1758 has better swimming ability due to its morphological characteristics (greater muscle and propulsion areas), suggesting that superior swimming capacity is based primarily on the development of muscles and other traits related to fish locomotion. Studies by Fisher et al (2000) showed similar results for the three reef fish species Pomacentrus amboinensis Bleeker, 1868, Sphaeramia nematoptera (Bleeker, 1856) and Amphiprion melanopus Bleeker, 1852. In these species, the critical swimming speed was positively correlated with the propulsion area.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Ohlberger et al (2006) verified that Mugil cephalus Linnaeus, 1758 has better swimming ability due to its morphological characteristics (greater muscle and propulsion areas), suggesting that superior swimming capacity is based primarily on the development of muscles and other traits related to fish locomotion. Studies by Fisher et al (2000) showed similar results for the three reef fish species Pomacentrus amboinensis Bleeker, 1868, Sphaeramia nematoptera (Bleeker, 1856) and Amphiprion melanopus Bleeker, 1852. In these species, the critical swimming speed was positively correlated with the propulsion area.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, this topic is relevant to the acquisition of food and the avoidance of predators (Videler, 1993), as well as to migration success (Fisher & Bellwood, 2003). Many morphological traits of the body of a fish are considered important for defining the swimming capacity, including the aspect and muscle ratios (Sambilay, 1990;Fisher et al, 2000), caudal peduncle depth factor (Webb & Weihs, 1986), propulsive ratio (Fisher et al, 2000), caudal fin length ratio (Nanami, 2007), and fineness ratio (Bainbridge, 1960;Webb, 1975;Blake, 1983;Scarnecchia, 1988). The body shape and the fin size can accurately indicate the behavior, swimming mode and habitat preferences of fish (Keast & Webb, 1966;Webb, 1984), providing a more accurate understanding of the fish's body shape and its structure and functions (Winemiller, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The onset of vertical migration behavior is initiated at flexion, which starts as early as 5 d after hatch for S. partitus (Paris-Limouzy 2001). At that stage, the gas bladder is already formed and active control by larva of this particular family is tangible (see Fisher et al [2000] for development of critical swimming speed). Tracers are then moved into the next 20-m layer every 5-d until they reach the last layer (80-100 m).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies of fish larvae highlight the impact that active swimming behaviour has on their dispersal patterns in both freshwater (Lechner et al 2014b(Lechner et al , 2016Schludermann et al 2012) and marine environments (Leis 2006;Fisher et al 2000; Leis and Carson-Ewart 1997). Dispersal modes of fish during the crucial larval phase of their life cycle is an important factor in recruitment and is governed by abiotic triggers (e.g., hydrology and hydraulics: Pavlov (1994); and discharge: Lechner et al 2017;Korman et al (2004); Reichard and Jurajda (2004)), in combination with biotic triggers (e.g., physiology and behaviour: Gaudin and Sempeski (2001); Heggenes and Dokk (2001);Pavlov (1994)).…”
Section: Introductionmentioning
confidence: 99%